2014
DOI: 10.1039/c4ra02359e
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effect on observation of nanostructural hydrated porous ceramic green bodies using hydrophilic ionic liquid

Abstract: A convenient characterization method of a nanostructural hydrated porous ceramic body using a hydrophilic ionic liquid is established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…As previous work has shown that b-lactones are prone to epimerisation at C(3) under basic reaction conditions, in situ reaction monitoring in CD 2 Cl 2 using 1 H NMR spectroscopic analysis demonstrated that the product b-lactone dr was invariant with time, presumably due to rapid epimerisation leading to equilibration. [24][25][26]28,57,58 Subsequent studies were aimed at in situ derivatisation to facilitate diastereoisomer separation and allow unambiguous determination of enantioselectivity. Interestingly, the use of benzylamine or pyrrolidine as a derivatisation agent gave an approximate 70 : 30 mixture of the corresponding diastereoisomeric b-hydroxyamides 9 and 10 (both in 99 : 1 er).…”
Section: Resultsmentioning
confidence: 99%
“…As previous work has shown that b-lactones are prone to epimerisation at C(3) under basic reaction conditions, in situ reaction monitoring in CD 2 Cl 2 using 1 H NMR spectroscopic analysis demonstrated that the product b-lactone dr was invariant with time, presumably due to rapid epimerisation leading to equilibration. [24][25][26]28,57,58 Subsequent studies were aimed at in situ derivatisation to facilitate diastereoisomer separation and allow unambiguous determination of enantioselectivity. Interestingly, the use of benzylamine or pyrrolidine as a derivatisation agent gave an approximate 70 : 30 mixture of the corresponding diastereoisomeric b-hydroxyamides 9 and 10 (both in 99 : 1 er).…”
Section: Resultsmentioning
confidence: 99%
“…Methods involving the use of ionic liquid (IL) and NanoSuit have recently been employed as new sample preparation methods for electron microscopy . In our previous studies, hydrous materials such as agar gel, seaweed, and bacterial cells have been observed using conventional TEM and field‐emission electron microscopy (FE‐SEM) with a hydrophilic IL . Recently, we have reported a method for the FE‐SEM observation of biofilms treated with polymeric nanoparticles (NPs).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In our previous studies, hydrous materials such as agar gel, seaweed, and bacterial cells have been observed using conventional TEM and field-emission electron microscopy (FE-SEM) with a hydrophilic IL. [9][10][11] Recently, we have reported a method for the FE-SEM observation of biofilms treated with polymeric nanoparticles (NPs). It was found that the developed sample preparation method with an IL enables the observation of fine morphologies of biological materials that have never been observed using conventional methods (i.e., ultrathin sectioning).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies also showed that some wet materials, including agar gel, hydrous hydroxyapatite green body, hydrous montmorillonite, and swelled seaweed, can be observed using an optimized method by FE-SEM and TEM. [29][30][31][32] In the present study, we tried to establish a preparation method of nanopolymeric micelles based on Soluplus® to cure of biolm infection disease. We describe the antibacterial activities against the biolm of four types of polymeric nanocarriers prepared using PLGA and Soluplus®.…”
Section: Introductionmentioning
confidence: 99%